Respostas
respondido por:
2
Resposta:
Sim
Explicação passo-a-passo:
Delta = b - 4*a*c
Delta = -(-4*1*9)
Delta = -(-36)
Delta = 36
Avalia como melhor resposta ಠ‿↼.
respondido por:
0
Resposta: Sim
Explicação passo-a-passo:
Eq. 2o grau: ay^2 + by + c = 0
então: a = 1, b = 0 e c = 9
Delta = b - 4*a*c
Delta = -(-4*1*9)
Delta = -(-36)
Delta = 36
Como o delta é positivo, a equação apresenta duas soluções reais.
marjoredias221:
obrigada
Perguntas similares
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás